Peran Program Infak Jum’at dalam Meningkatkan Empati Siswa Kelas XII di SMAN 7 Kota Bogor - Wulan Anggraini; Sri Nurul Milla; Nurman Hakim (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Islam teaches us to empathize with one another. One of the things that can be expected to boost student empathy is the activity of infaking. The objective of this study is to: 1) To find out how the implementation of the infak program on Friday in the SMAN 7 city of Bogor, 2) To know how the role of the program infak in improving the empathy of the students of the 12th grade in the S.M. 7 city Bogor. The type of research used is qualitative with a descriptive approach. Data collection using interviewing techniques by interviewing 3 teachers and verifying data is triagulated by interviews with 5 students and the data obtained is analyzed using data reduction. The results of data analysis found 7 themes, namely: (1). Friday (2). IRMA (3). Volunteering (4). Social funds (5). Increasing sensitivity to others (6). Understanding others (7). Increase awareness of others. This infak program is judged to enhance empathy among students of the 12th grade in the 7th grade school of Bogor and needs to be re-optimized by the school to build a culture of empathism and teach students about social values such as caring and sharing, both in terms of equality, guidance and learning activities teaching and applying empathic attitudes in everyday life consistently